Economic Governance of Railways in a Federation - Wills-Johnson, Nick (John Curtin Institute of Public Policy, 2007)
Until recently, Australia?s State Government-owned railways operated almost entirely within their home states. This has begun to change, in response to the new dynamics unleashed by economic and structural reforms which began in the 1990s. The economic regulatory system that governs third party access to track infrastructure is still a mix of State and Federal regulation, which has lead to calls for greater consistency. However, it is not clear how much centralisation is optimal. This paper examines railway governance from an historical and a functional perspective, and argues that the best approach is not technocratic, but institutional